2000
DOI: 10.2337/diabetes.49.5.832
|View full text |Cite
|
Sign up to set email alerts
|

Genotype/phenotype relationships in HNF-4alpha/MODY1: haploinsufficiency is associated with reduced apolipoprotein (AII), apolipoprotein (CIII), lipoprotein(a), and triglyceride levels.

Abstract: Hepatocyte nuclear factor (HNF)-4␣ is a transcription factor that plays an important role in regulation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
86
2
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 38 publications
10
86
2
2
Order By: Relevance
“…ApoCIII is an HNF4α target gene, as demonstrated by in vitro promoter analyses [56,57] and verified by the decreased expression of ApoCIII in a liver HNF4α-deficient mouse model [2,6] and in human patients with mutations in HNF4α [58]. In the present study, HNF4α activated the human ApoCIII promoter in HepG2 hepatoma cells, and to an even greater extent in COS-1 cells, which are devoid of the low level of endogenous HNF4α found in HepG2 cells.…”
Section: Discussionsupporting
confidence: 79%
“…ApoCIII is an HNF4α target gene, as demonstrated by in vitro promoter analyses [56,57] and verified by the decreased expression of ApoCIII in a liver HNF4α-deficient mouse model [2,6] and in human patients with mutations in HNF4α [58]. In the present study, HNF4α activated the human ApoCIII promoter in HepG2 hepatoma cells, and to an even greater extent in COS-1 cells, which are devoid of the low level of endogenous HNF4α found in HepG2 cells.…”
Section: Discussionsupporting
confidence: 79%
“…Two non-carrier subjects of the A232D pedigree had triglyceride levels of 1.17 and 1.25 mmol/l, suggesting that triglyceride levels may be lower in subjects with these two GCK mutations. The triglyceride level (mean 0.84 mmol/l) in the 15 MODY2 carriers is similar to that observed in 18 carriers of the RW/MODY1 pedigree (mean 0.80 mmol/l) [2]. In contrast, the triglyceride concentrations were normal in a very large series of primarily French MODY2 patients (mean BMI 22.0) [7].…”
supporting
confidence: 75%
“…This is illustrated by studies of apolipoproteins in different MODY1 pedigrees with various mutations of the gene encoding hepatocyte nuclear factor 4α (HNF4A). The mean plasma triglyceride concentration was significantly lower in 18 subjects (mean BMI 24.0) of the Michigan RW pedigree with the Q268X mutation (mean 0.80 mmol/l) [2] and in six subjects (mean BMI 24.0) from a Swedish family with the K99fsdelAA mutation (mean 0.64 mmol/l) [3] compared with 1.39 and 1.36 mmol/l, respectively, in control groups matched for BMI. The 18 RW subjects also had significantly lower lipoprotein(a) concentrations (mean 0.31 mmol/l) compared with the 24 control subjects (1.16 mmol/l).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Mutation in the HNF-4␣ gene in MODY1 impaired triacylglycerol metabolism and insulin secretion. Shih et al (38) reported that serum levels of ApoAII, ApoCIII, lipoprotein(a), and triacylgylcerol were significantly reduced in diabetic patients with HNF-4␣ mutations compared with these levels in matched diabetic patients. Mice lacking hepatic HNF-4␣ expression accumulated lipid in the liver and exhibited greatly reduced serum cholesterol and triacylglycerol levels (39).…”
Section: Adenovirus-mediated Hnf-4␣ Genementioning
confidence: 99%